The interplay between conformation and absolute configuration in chiral electron dynamics of small diols - Daly, Stephen; Tia, Maurice; Garcia, Gustavo A.; Nahon, Laurent; Powis, Ivan (Wiley-VCH Verlag, 2016)
A competition between chiral characteristics alternatively attributable to either conformation or to absolute configuration is identified. Circular dichroism associated with photoexcitation of the outer orbital of configurational enantiomers of 1,3- and 2,3-butanediols has been examined with a focus on the large changes in electron chiral asymmetry produced by different molecular conformations. Experimental gas phase measurements offer support for the theoretical modelling of this chiroptical effect. A surprising prediction is that a conformationally produced pseudoenantiomerism in 1,3-butanediol generates a chiral response in the frontier electron dynamics that effectively outweighs the influence of the permanent configurational handedness established at the asymmetrically substituted carbon. Induced conformation, and specifically induced conformational chirality, may thus be a dominating factor in chiral molecular recognition in such systems.